Perceptions and Performance of dental students using Conventional and Virtual Microscopy in Oral Pathology - Gulmina Saeed Orakzai; Waqar-Un-Nisa; Saima Irshad; Nabeela Naeem; Ammarah Afreen; Zarah Afreen (Journal of Rawalpindi Medical College)
Virtual microscopy for showing histopathological slides have been in use for quite some time. This method of teaching is considered to be a good replacement for conventional microscopy using glass slides. This study was carried out to analyze the perception and performance of dental students regarding the use of conventional microscopic slides and virtual slides in relation to teaching and learning.